Transformation of Boarding School Management Models in Enhancing Student Accessibility and Educational Quality - Darwanto, Agus; Prahmana, Rully Charitas Indra; Susanti, Ani; Khalil, Ibrahim Alhussain (Jurnal Pendidikan Agama Islam, 2024)
Purpose – Boarding schools in Indonesia integrate Islamic religious education with general education, offering a comprehensive learning and living experience for students. This model is effective in character building, moral value reinforcement, tolerance promotion, social integrity, and responsibility, all while emphasizing knowledge and technology mastery. However, these schools face challenges, including high costs, geographical barriers, and stringent academic requirements that limit accessibility for some students. This research underscores the need for management transformation in boarding schools to enhance accessibility and education quality while preserving the unique values and identity of pesantren. Design/methods/approach – Utilizing a literature review methodology, this study critically summarizes and evaluates relevant research to provide a comprehensive understanding of the transformation of boarding school management in Indonesia. Findings – The findings indicate that boarding schools must adapt to socio-cultural contexts and incorporate information and communication technology into management and learning processes. The study also reveals that parental involvement, effective management, and support for students' mental and physical health are crucial for the success of boarding schools. Research implications/limitations – Future research should focus on integrating ICT to improve educational outcomes and administrative efficiency, assessing holistic education models, evaluating economic empowerment programs, and examining mental health initiatives, as well as exploring collaborative efforts to enhance community engagement and support for students. Originality/value – Strengthening pesantren culture can address issues such as bullying, poor nutrition, and financial difficulties. Transformational management practices can meet the evolving educational needs and dynamic desires of parents and students while maintaining the core values of pesantren in Indonesia.